Prevalence and Risk Factors of Restless Legs Syndrome among Chinese Adults in a Rural Community of Shanghai in China - Shi, Yunbo (PLoS One, 2015)
AIMS: The primary objective of this study was to investigate the prevalence and risk factors of restless legs syndrome (RLS) in an adult Chinese population living in a rural community. We also aimed to determine the predictive diagnostic value of the 4-item screening questionnaire for RLS in this population. METHODS: This study was designed as a 2-phase survey. In phase 1 we performed a face-to-face interview of eligible individuals living in a rural community in Shanghai using a 4-item screening questionnaire. In phase 2, sleep specialists performed a phone interview of the individuals who screened positive to diagnosis RLS. RESULTS: Forty-one RLS cases were confirmed among 2941 eligible individuals 18 years of age or older in the study community. The prevalence of RLS was 1.4% (95% confidence interval (CI) =1.0-1.9%), with a significantly higher rate observed in females (1.9% [95%CI =1.3-2.7%]) than that in males (0.9% [95%CI =0.5-1.5%], p=0.019). The prevalence rate increased significantly with age, from 0.2% (95% CI =0.08-0.6%) in those 18-39 years old to 4.1% (95% CI =2.1-7.9%) in those ≥70 years old (p<0.001). The multivariate logistic regression analysis indicated that gastritis, anemia and hypertension were risk factors for RLS. The sensitivity and specificity of the 4-item screening questionnaire used in this study were 63.4% and 97.5%, respectively. CONCLUSION: RLS prevalence is relatively low among Chinese adults living in rural Shanghai. Furthermore, population-based studies with a larger sample size and a longitudinal follow-up may help to determine the risk factors of RLS and potential interventions for RLS.